2019
DOI: 10.1111/nph.15670
|View full text |Cite
|
Sign up to set email alerts
|

A pool‐weighted perspective on the two‐water‐worlds hypothesis

Abstract: Summary The ‘two‐water‐worlds’ hypothesis is based on stable isotope differences in stream, soil and xylem waters in dual isotope space. It postulates no connectivity between bound and mobile soil waters, and preferential plant water uptake of bound soil water sources. We tested the pool‐weighted impact of isotopically distinct water pools for hydrological cycling, the influence of species‐specific water use and the degree of ecohydrological separation. We combined stable isotope analysis (δ18O and δ2H) of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 61 publications
4
56
0
Order By: Relevance
“…2). While winter isotopic signatures have previously been observed in summer xylem of desert plants (Ehleringer et al, 1991), our work demonstrates the widespread use of winter water in midsummer across diverse humid climates, prompting the question of how much does tree water use depends on summer rainfall.…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…2). While winter isotopic signatures have previously been observed in summer xylem of desert plants (Ehleringer et al, 1991), our work demonstrates the widespread use of winter water in midsummer across diverse humid climates, prompting the question of how much does tree water use depends on summer rainfall.…”
Section: Resultsmentioning
confidence: 51%
“…Water stable isotope signatures (δ 2 H and δ 18 O) have been used as tracers to show that plant water uptake is not sourced from the same subsurface storage as streamflow (Evaristo et al, 2015;Good et al, 2015;Javaux et al, 2016), but it remains unclear how that storage is replenished and becomes available to plants. Soils may retain a mixture of waters that originate from many previous precipitation events (Botter et al, 2011;Mueller et al, 2014;Sprenger et al, 2016b;Brinkmann et al, 2018), but plants may not evenly sample from that distribution of water ages, because plants may root such that they preferentially take up water moving along faster or slower pathways (Brooks et al, 2010;Ehleringer et al, 1991;Stewart et al, 1999). These interactions between root distributions and infiltration dynamics could hypothetically result in plants disproportionally using precipitation from past seasons rather than recent precipitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, xylem water will reflect the mixture of different water ages taken up by the plant. It has been shown that the uptake of a small proportion of highly evaporatively enriched water from the upper soil surface, that is, often the soil layer with the highest nutrient concentrations, can markedly change the xylem water isotopic signature, even when bulk water uptake derives from deeper soil layers with higher water content (Dubbert et al, ). Moreover, it needs to be taken into account that root water uptake is a passive process following a water potential gradient.…”
Section: How Interfaces Affect Water Age Distributionsmentioning
confidence: 99%
“…Plants can access shallow and deep soil water, as well as groundwater with a tendency to prioritize the use of stable and continuous water sources (Zhao & Wang, ), at least in regions where some sources are continuously available. Several studies based on an isotope approach and focusing on the identification of different water sources accessed by plants have been conducted at individual sites in many regions of the world and on different plant species (e.g., to name a few recent studies, Allen, Kirchner, Braun, Siegwolf, & Goldsmith, ; Chi, Zhou, Yang, Li, & Zheng, ; Dubbert, Caldeira, Dubbert, & Werner, ; Evaristo et al, ; Nie et al, ; Oerter, Siebert, Bowling, & Bowen, ; Qiu et al, ). Recent meta‐analyses assessed plant water sources across different biomes and plant species (Barbeta & Peñuelas, ; Evaristo, Jasechko, & McDonnell, ; Evaristo & McDonnell, , ).…”
Section: Introductionmentioning
confidence: 99%